Peran Jasa Ground Handling Terhadap Pelayanan Perusahaan Air Freight di Bali dalam Menghadapi Kompetisi Global - Yati Nurhayati; Yunitha Ardiani Nur (WARTA ARDHIA, 2016)
Salah satu kunci keberhasilan dari sebuah perusahaan pengiriman barang terletak pada kegiatan handling barang yang efektif dan efisien. Untuk dapat berkompetisi dengan baik dengan acuan waktu pelayanan yang efisien, perusahaan jasa airfreight memerlukan kerjasama dengan perusahaan jasa ground handling (PT Jasa Angkasa Semesta dan PT Gapura Angkasa) agar dapat memenuhi kebutuhan pelanggan. Di sinilah letak peran penting perusahaan jasa ground handling terhadap bisnis air cargo. Sesuai dengan konsep aliran logistik secara terpadu maka selayaknya tidak ada sekat (boundary) atau pisahan antara perusahaan jasa ground handling dan airfreight dalam operasionalnya. Keduanya bersama-sama dengan maskapai penerbangan merupakan satu kesatuan untuk tujuan yang sama mengirim cargo pelanggan tepat waktu. Strategi apa yang akan digunakan perusahaan jasa airfreight bergantung kepada perhitungan IFAS dan EFAS untuk mencari titik absis dan ordinat yang menunjukkan posisi strategis perusahaan airfreight saat ini. Sebagai alat analisis kualitatif, analisis SWOT (Strength, Weaknesses, Opportunities, dan Threat) memadai untuk mengetahui posisi strategis perusahaan airfreight dan mengatur langkah strategi apa yang akan digunakan. Kerjasama antara airfreight dan ground handling ini diharapkan akan menghasilkan jasa pelayanan air cargo dengan total waktu proses yang relatif cepat. [The Role of Ground Handling Services to The Air Freight Services in Bali in The Face of Global Competition] One of the successful key of freight forwarder companies lies in their handling operations that executed effectively and efficiently. Most of the companies that can stay competitive in this transportation services business are those which operated with relatively short time in unloading and loading the cargo. In order to make their companies well competed with reference to efficient services time, air freight services companies need to cooperate with ground handling services companies (PT Jasa Angkasa Semesta and PT Gapura Angkasa) so that customer needs can be fulfilled. And that is the important role of ground handling services in the air freight business. In accordance with the integrated logistic flow concept, there should be no operational boundaries between ground handling services companies and air freight services companies. Both of them, together with the airlines, are an entity with the same purpose: to handle the customer cargo right in time. The strategy that will be used by air freight services companies rely on IFAS and EFAS calculation in order to find the correct abscissa and ordinate that indicate the strategic position of the companies at the moment. SWOT (Strengths, Weaknesses, Opportunities, and Threats) used as the tool of qualitative analysis not only for indicating the strategic position of the air freight services companies but also for managing the strategic measures that will be taken. The awareness of strengths, weaknesses, opportunities, and threats of the air freight services companies can be used as the benefit in the cooperation with the other services companies, especially ground handling and airlines. The role of ground handling in improving the strengths and using the opportunities while reducing weaknesses and threats is crucial for air freight operations. Thus, cooperation between air freight and ground handling is expected in providing quick processing-cargo services.